Bachelor of Science in Rangeland Ecosystem Management Curriculum - Mwamburi, Mcharo; Kambura, Ann; Gacheru, James; Maghenda, Marianne; Jalang'o, Dorcas; Waswa, Boaz Shaban; Kinyua, Ivy Wambui; Templer, Noel; Mwongera, Caroline (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The School of Agriculture, Earth and Environmental Sciences strongly believes in supporting advances in various aspects of rangeland science and community development practices in the rangeland ecosystem. There is increasing need to have well trained personnel with expertise in sustainable rangeland management, to provide leadership and stewardship for a sustainable framework for managing rangelands. This paradigm underlies the philosophy of linking the programme delivery with hands-on training, support to applied research and policy support ability to effectively contribute to sustainable rangeland ecosystem development and management. Universities have a key role in providing technical support in theory and practice by being proactive in training, research and innovation for sustainable rangeland resource management. This degree programme will contribute to the goal of improving the rangeland ecosystem health, while supporting sustainable livelihood options of communities and biodiversity in these ecosystems.